A GENDER SENSITIVE FRAMEWORK TO SAFETY AND HEALTH AT WORK - Masike, Rujeko; Mwanza, Bupe; Masiyazi, Lodrina (European Scientific Journal, ESJ, 2014)
The aim of this paper was to formulate a strategy on how to take agender sensitive approach when negotiating health and safety policies andprocedures in the workplace. This was done by carrying out case studies onhow companies are managing gender in their occupational health and safetypolicies, thereby highlighting the different health and safety risks that femaleand male workers are exposed to. The methodology was based on astructured questionnaire and direct observations to gather information fromcompanies within a Southern African case country. Women’s response to thequestionnaire and the content of their answers were quite different fromthose of their male colleagues, indicating that industry is defined, to a largeextent, in gender terms as far as working conditions are concerned. Literaturefrom researches that have been carried out on occupational safety and health(OSH) pertaining to gender was reviewed. and it described differences inhealth at work by gender accounting for both psychosocial and physicalhazards at work. The paper outlined a set of interesting lessons foracademics, industry and safety practitioners by providing guidelines that willassist in ensuring a correct focus to select an appropriate safety performanceevaluation model.